Nanoparticle exposure reactivates latent herpesvirus and restores a signature of acute infection. Issue 1 (December 2017) - Sattler, Christine; Moritz, Franco; Chen, Shanze; Steer, Beatrix; Kutschke, David; Irmler, Martin; Beckers, Johannes; Eickelberg, Oliver; Schmitt-Kopplin, Philippe; Adler, Heiko; Stoeger, Tobias
Abstract Background Inhalation of environmental (nano) particles (NP) as well as persistent herpesvirus-infection are potentially associated with chronic lung disease and as both are omnipresent in human society a coincidence of these two factors is highly likely. We hypothesized that NP-exposure of persistently herpesvirus-infected cells as a second hit might disrupt immune control of viral latency, provoke reactivation of latent virus and eventually lead to an inflammatory response and tissue damage. Results To test this hypothesis, we applied different NP to cells or mice latently infected with murine gammaherpesvirus 68 (MHV-68) which provides a small animal model for the study of gammaherpesvirus-pathogenesis in vitro and in vivo. In vitro, NP-exposure induced expression of the typically lytic viral gene ORF50 and production of lytic virus. In vivo, lytic viral proteins in the lung increased after intratracheal instillation with NP and elevated expression of the viral gene ORF50 could be detected in cells from bronchoalveolar lavage. Gene expression and metabolome analysis of whole lung tissue revealed patterns with striking similarities to acute infection. Likewise, NP-exposure of human cells latently infected with Epstein-Barr-Virus also induced virus production. Conclusions Our results indicate that NP-exposure of persistently herpesvirus-infected cells – murine or human – restores molecular signatures found in acute virus infection, boosts production of lytic viral proteins, and induces an inflammatory response in the lung – a combination which might finally result in tissue damage and pathological alterations.